The G Protein-Coupled Estrogen Receptor Agonist G-1 Inhibits Nuclear Estrogen Receptor Activity and Stimulates Novel Phosphoproteomic Signatures. (29th March 2016) - Smith, L. Cody; Ralston-Hooper, Kimberly J.; Ferguson, P. Lee; Sabo-Attwood, Tara
Abstract: Estrogen exerts cellular effects through both nuclear (ESR1 and ESR2) and membrane-bound estrogen receptors (G-protein coupled estrogen receptor, GPER); however, it is unclear if they act independently or engage in crosstalk to influence hormonal responses. To investigate each receptor's role in proliferation, transcriptional activation, and protein phosphorylation in breast cancer cells (MCF-7), we employed selective agonists for ESR1 propyl-pyrazole-triol (PPT), ESR2 diarylpropionitrile (DPN), and GPER (G-1) and also determined the impact of xenoestrogens bisphenol-A (BPA) and genistein on these effects. As anticipated, 17β-estradiol (E2), PPT, DPN, BPA, and genistein each enhanced proliferation and activation of an ERE-driven reporter gene whereas G-1 had no significant impact. However, G-1 significantly reduced E2-, PPT-, DPN-, BPA-, and genistein-induced proliferation and ERE activation at doses greater than 500 nM indicating that G-1 mediated inhibition is not ESR isotype specific. As membrane receptors initiate cascades of phosphorylation events, we performed a global phosphoproteomic analysis on cells exposed to E2 or G-1 to identify potential targets of receptor crosstalk via downstream protein phosphorylation targets. Of the 211 phosphorylated proteins identified, 40 and 13 phosphoproteins were specifically modified by E2 and G-1, respectively. Subnetwork enrichment analysis revealed several processes related to cell cycle were specifically enriched by G-1 compared with E2. Further there existed a number of newly identified proteins that were specifically phosphorylated by G-1. These phosphorylation networks highlight specific proteins that may modulate the inhibitory effects of G-1 and suggest a novel role for interference with nuclear receptor activity driven by E2 and xenoestrogens.